2018
DOI: 10.17533/udea.rccp.v31n1a05
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum testosterone, sperm production, and testis traits with fertility of Mangalarga Marchador stallions

Abstract: Relación entre testosterona sérica, producción espermática y características testiculares con la fertilidad en sementales Mangalarga Marchador Relação entre testosterona sérica, produção espermática e características testiculares com fertilidade em garanhões Mangalarga MarchadorAbstract Background: Assessing breeding soundness is important to predict the potential fertility of stallions. Objective: To investigate the association of testis traits, total number of spermatozoa, and testosterone with fertility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The range of minimum and maximum of the testicular traits were in general low, suggesting lower variations among stallions. The pro le of the Pantaneiro testicular biometry has not been reported before, then we are bringing new informations.Comparing the values of testis biometry of Pantaneiro stallions from this study with others we could note that means of left and right testicular length (8.6 ± 0.2 and 8.5 ± 0.2 respectively) were similar to means of LTL and RTL reported byRua et al (2018), studying Mangalarga Marchador stallions in Brazil. However, the mans of LTW, RTW, LTH and RTH were lower in the present study.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The range of minimum and maximum of the testicular traits were in general low, suggesting lower variations among stallions. The pro le of the Pantaneiro testicular biometry has not been reported before, then we are bringing new informations.Comparing the values of testis biometry of Pantaneiro stallions from this study with others we could note that means of left and right testicular length (8.6 ± 0.2 and 8.5 ± 0.2 respectively) were similar to means of LTL and RTL reported byRua et al (2018), studying Mangalarga Marchador stallions in Brazil. However, the mans of LTW, RTW, LTH and RTH were lower in the present study.…”
supporting
confidence: 85%
“…Therefore, the Pantaneiro horse seminal traits were less explored and few information are available to refers them. The evaluation of testis biometry associated with seminal characteristics provide informations about the sperm production and sperm quality witch can allow the selection of stallions with better seminal traits to reproduction (Rua et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, McKinnon et al (2011) found the percentage of testicular cells and testicular volume tends to increase with the advancement of age in the horse. On the contrary, age did not affect testis traits in the horse (Rua et al, 2018). This difference might be attributed to species difference, sample size and biological variability between animals.…”
Section: Discussionmentioning
confidence: 98%